One-pot synthesis of nanomaterials via RAFT polymerization induced self-assembly and morphology transition - Wan, Wen-Ming; Hong, Chun-Yan; Pan, Cai-Yuan (Chemical communications (Cambridge, England), 2009)
A simple and facile strategy has been developed for synthesis of nanomaterials via polymerization in high concentration; multiple morphologies can be created and tuned just by variation of the feed ratio and reaction conditions.